Inhaled PAMAM-based nano-formulation prolonged lung retention for alleviating pulmonary inflammation of COPD - Chen Wang; Xiao-yan Hu; Ri Ji; Yi-fan Lu; Xiang Shen; Zhang Wang; Fei Wang; Guo-chao Shi; Yun Feng (Materials Today Bio)
Chronic obstructive pulmonary disease (COPD) stands as a predominant respiratory disorder intricately linked with respiratory tract microorganisms and their metabolites. Indole acetic acid (IAA), a derivative of tryptophan produced by Lactobacillus salivarius, possesses notable anti-inflammatory properties. However, the short retention time of the drug in lung still remains a vital obstacle leading to a poor bioavailability. In this study, we innovatively engineer a nano-composite by coupling IAA with generation 4 polyamidoamine (G4 PAMAM) dendrimer to form G4-IAA nano-complex through host-guest interaction. G4-IAA shows significantly improved solubility of IAA and thus enhances its bioavailability. This G4-IAA complex facilitates direct aerosol-based pulmonary administration by inhaled strategy, exhibiting enhanced absorption by respiratory epithelial cells and prolonged lung retention. Our experimental findings reveal that inhalation therapy employing the G4-IAA complex mitigates inflammatory stress and augments pulmonary function in COPD murine models. Single-cell sequencing reveals macrophages may contribute to the functional shifts by G4-IAA, promoting an anti-inflammatory phenotype characteristic of M2 polarization. This research introduces a promising therapeutic strategy, offering improved symptomatic relief and reduced risk of acute exacerbations for individuals afflicted with COPD.